2021
DOI: 10.14814/phy2.15106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of changes in end‐tidal PO 2 and PCO 2 on neural responses during rest and sustained attention

Abstract: Impairments of cognitive function during alterations in arterial blood gases (e.g., high‐altitude hypoxia) may result from the disruption of neurovascular coupling; however, the link between changes in arterial blood gases, cognition, and cerebral blood flow (CBF) is poorly understood. To interrogate this link, we developed a multimodal empirical strategy capable of monitoring neural correlates of cognition and CBF simultaneously. Human participants performed a sustained attention task during hypoxia, hypercap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…The critical importance of pCO2V homeostasis for brain cognitive and electrical function has been long known from patient studies (Meyer et al, 1966). More recently, magneto/electro‐encephalography (MEG/EEG), as well as resting state functional magnetic resonance (fMRI) studies, have found that small (few torr) increases in end‐tidal pCO2 significantly alter brain electrical activity (Driver et al, 2016; Hall et al, 2011; Halpern et al, 2003; Jones et al, 2005; Xu et al, 2011; Zappe et al, 2008) as well as cognitive function (Bullock et al, 2021). In the most sensitive measurements performed, MEG measurements during hypercarbia found the level of spontaneous neural oscillations in alpha (8–13 Hz), beta (13–30 Hz) and low gamma (30–50 Hz) band power is altered by end‐tidal pCO2 changes of as little as 240.25emtorr (Driver et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The critical importance of pCO2V homeostasis for brain cognitive and electrical function has been long known from patient studies (Meyer et al, 1966). More recently, magneto/electro‐encephalography (MEG/EEG), as well as resting state functional magnetic resonance (fMRI) studies, have found that small (few torr) increases in end‐tidal pCO2 significantly alter brain electrical activity (Driver et al, 2016; Hall et al, 2011; Halpern et al, 2003; Jones et al, 2005; Xu et al, 2011; Zappe et al, 2008) as well as cognitive function (Bullock et al, 2021). In the most sensitive measurements performed, MEG measurements during hypercarbia found the level of spontaneous neural oscillations in alpha (8–13 Hz), beta (13–30 Hz) and low gamma (30–50 Hz) band power is altered by end‐tidal pCO2 changes of as little as 240.25emtorr (Driver et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Statistical significance in all tests (except the rank order analysis) was assessed by using a non-parametric permutation-based resampling approach to empirically approximate null distributions for F and t statistics ( Foster et al, 2016 ; Bullock et al, 2017 ; Bullock et al, 2021 ). This testing approach was adopted because it has the advantage of being robust to violations of normality.…”
Section: Methodsmentioning
confidence: 99%
“…These studies suggest that circular breathwork increases blood oxygenation (Bednarczyk et al, 1990;Zwaag et al, 2022) while reducing CO2 saturation (Bednarczyk et al, 1990;Inbar et al, 2022;Kox et al, 2014;Krapf et al, 1991;Stäubli et al, 1994;Tercero et al, 2021;Zwaag et al, 2022). This in turn renders blood pH more alkaline (respiratory alkalosis, (Bednarczyk et al, 1990;Kox et al, 2014;Krapf et al, 1991;Nuding et al, 2015;Stäubli et al, 1994;Zwaag et al, 2022)), causing vasoconstriction (Ainslie & Duffin, 2009;Bednarczyk et al, 1990;Bullock et al, 2021;Ito et al, 2003;Kety & Schmidt, 1946;Kontos et al, 1977;Mueller et al, 1977;Stäubli et al, 1994;K. Szabo et al, 2011;Tercero et al, 2021), particular throughout the neocortex (Posse et al, 1997;Terekhin & Forster, 2006;Wise et al, 2007).…”
Section: Introductionmentioning
confidence: 99%